ANALYSIS OF MATHEMATICS TEXTBOOKS FOR THE INDEPENDENT CURRICULUM OF FLAT BUILDING MATERIALS BASED ON BELL CRITERIA FOR GRADE IV AT SDN GAROT ACEH BESAR - Amalia, Annisa; Fauzi, Fauzi; Yamin, M. (Elementary Education Research, 2024)
The research aims to determine the suitability of the Merdeka Curriculum Mathematics Textbook for Flat Building Materials Based on the Class IV Bell Criteria in terms of the suitability of the material, method of delivering the material, physical characteristics, and instructions for teachers based on the Bell Criteria. The approach used in this research is qualitative with descriptive research type. Data collection was carried out using textbook assessment sheets based on Bell's criteria, taking into account aspects of material suitability, material delivery methods, physical characteristics, and instructions for teachers. The results of the research show that the conformity of textbooks is based on the bell criteria relating to mathematics material. Of the 21 indicators, there are 14 appropriate indicators and 7 indicators that are not appropriate in the good category with a conformity percentage of 70%; related to the method of delivering material, of the 21 indicators, there are 16 indicators that are suitable and 5 indicators that are not suitable in the good category with a suitability percentage of 76.1%; related to the physical characteristics of the 11 indicators, there are 10 indicators that are suitable and there is 1 indicator that is not suitable in the very good category with a suitability percentage of 90.9%; and related to instructions for teachers, of the 19 indicators, there are 12 appropriate indicators and 7 indicators that are not appropriate in the good category with a conformity percentage of 63.1%. Based on the results of this research, it can be concluded that the mathematics textbook for the independent curriculum on flat figures based on class IV bell criteria has fulfilled the aspects of assessing the suitability of the material, method of delivering the material, physical characteristics, and instructions for teachers based on the bell criteria.